Impact of the regulation (EU) 1169/2011: Allergen-related recalls in the rapid alert system for food and feed (RASFF) portal - Pádua, I. (2019)
Introduction: Food allergy is a public health concern and the information on food allergens incidents, including data provided by RASFF (Rapid Alert System for Food and Feed) portal, is crucial for risk management. Aim: Our aim is to analyse the data in RASFF portal to determine a correlation between the notifications related to food allergens and the entering into force of the Regulation (EU) No 1169/2011. Methods: All allergen hazard notifications recorded in the RASFF were extracted for the period between 31/12/2011 and 31/12/2017 and information on notification type; allergen; product category; country notifying; notification basis and action taken was analysed. Results: A total of 627 notifications were reported and a significantly higher number of reports were observed in the last three years. Cereals and bakery products were the most reported categories and the main allergens were milk, cereals containing gluten and eggs. Official control on the market and company's own check were the main basis of the notifications and most frequently taken actions were recall from consumers and withdrawal of the product from the market. Conclusion: The increase in notifications in the last three years might be related to EU Regulation (EU) No 1169/2011. RASFF data can be a useful EU tool to improve allergen risk management, and highlights the call for action in food allergy education and training in the food systems and industry. © 2018 Elsevier Ltd